2019
DOI: 10.1038/s41598-019-40987-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of C-Reactive Protein with Risk of Developing Type 2 Diabetes Mellitus, and Role of Obesity and Hypertension: A Large Population-Based Korean Cohort Study

Abstract: This study was undertaken to assess the associations of C-reactive protein (CRP) with incident type-2 diabetes mellitus (T2DM) and to determine the joint effect of obesity and hypertension on them in the large-scale population-based Korean cohort of the Korean Genome and Epidemiology study (KoGES). We included 22,946 men and women from 11 rural communities at baseline (2005–2011). Epidemiological data and blood samples were collected. Incident physician-diagnosed T2DM cases (130 men and 148 women) were self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
40
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 31 publications
(42 reference statements)
7
40
4
2
Order By: Relevance
“…Hs-CRP concentrations increased with prolonged duration of diabetes in our study which is in line with the studies of [2,3,5,9,10,11] which reported a relationship between duration of diabetes, increased hs-CRP concentrations and resultant chronic inflammation. However, Wong et al, 2010 found a correlation between Hs-CRP levels and DOD in females only.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hs-CRP concentrations increased with prolonged duration of diabetes in our study which is in line with the studies of [2,3,5,9,10,11] which reported a relationship between duration of diabetes, increased hs-CRP concentrations and resultant chronic inflammation. However, Wong et al, 2010 found a correlation between Hs-CRP levels and DOD in females only.…”
Section: Discussionsupporting
confidence: 93%
“…Lipid profile among patients was within normal limits in our study. We observed a positive correlation between hs-CRP concentrations, triglycerides, TC and LDL-C as reported in studies [10][11][12][13][14]. This may be linked to the established association between systemic inflammation and lipid status in patients with diabetes and the fact that none of the patients recruited for our study was taking oral antihypertensive medication which is known to be associated with lower risk of obtaining elevated hs- Body mass index correlated positively with age, systolic blood pressure, diastolic blood pressure and waist circumference.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this study are in aggrement with other studies. Gambineri and Pelusi [30] reported that inflammation associated with T2D is more prominent in diabetic women due to hyperandrogenism which contributes to abdominal obesity; insulin sensitivity which influences the finding is accordance with Kanmani et al, [29] that reported higher level of CRP in women due to excess adiposity. Also elevated level was reported by Svensson et al, [26] in female type 2 diabetics.…”
Section: Discussionsupporting
confidence: 80%
“…Also, Cardoso et al, [28] showed higher CRP which was significantly associated with younger age less than eighty years. Kanmani et al, [29] reported that the association between C-reactive protein and incidence of type 2 diabetes mellitus which is more prominent among subjects from fifty years due to severe inflammation. The current study found gender difference in the level of C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%